Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.15537/smj.2020.6.25084
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the utilization of packed red blood cells stock in maternity hospitals

Abstract: Objectives: To assess and enhance the efficiency of transfusion services in maternity hospitals. Methods: A case control study was conducted from January to December 2016. A corrective policy of replacing preoperative type and hold step with blood transfusion request (BTR) hold was used only on healthy patients undergoing elective cesarean sections (c-section). The crossmatch/transfusion (C:T) ratio and a cost comparison were the evaluating factors. Data were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There are few studies from Saudi Arabia regarding blood bank utilization, and most include small sample sizes and short follow-up periods [2,[7][8][9][10]. A study on blood bank utilization conducted in our center between 1996 and 2000 showed an average C/T ratio of 2.96, which did not meet the international standards of less than 2, and over-ordering of blood products and cancellation of over 60% of transfusions [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies from Saudi Arabia regarding blood bank utilization, and most include small sample sizes and short follow-up periods [2,[7][8][9][10]. A study on blood bank utilization conducted in our center between 1996 and 2000 showed an average C/T ratio of 2.96, which did not meet the international standards of less than 2, and over-ordering of blood products and cancellation of over 60% of transfusions [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce blood wastage and enhance stock management, a number of low-cost policies can be implemented. These include improved communication between blood banks and providers ( Levin et al, 2019 , Mishra et al, 2021 ), staff continual education ( Burk et al, 2021 ), improved transport Kron et al, 2021 ), and updating transfusion protocols ( Bawazir and Dakkam, 2020 , Gholami et al, 2021 ) which all have been proven to have a cumulative effect in reducing blood wastage.…”
Section: Discussionmentioning
confidence: 99%
“…It would be very interesting and informative to see how they roll that out in their institution, and what challenges or facilitators they identified in that process. Although a cost analysis on the unused crossmatched blood was not performed in this study, other studies in the literature have demonstrated the cost benefit to more judicious preparation of crossmatched blood ( 12 ).…”
mentioning
confidence: 99%